Los derechos sociales desde la perspectiva de los derechos fundamentales (2004)
This article aims at expounding –from within the juridical theory– a basis to the social rights and at highlighting those latter in the Colombian Constitutional context in a way where we would advance towards acknowledging that social rights are of obligatory compliance to all powers and deserve juridical protection.At a first instance, the basic rights are approached from the formal point of view with their implications on social rights; then the Colombian Constitutional ordinance is examined. On the other hand, basic rights are analyzed from the material point of view with their influence over the realisation of social rights, in order to allow us, therefore, to propose concrete conclusions.